2006
DOI: 10.1093/cercor/bhl128
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Anatomical Evidence for Multisensory Interactions in Auditory Cortex

Abstract: Recent studies, conducted almost exclusively in primates, have shown that several cortical areas usually associated with modalityspecific sensory processing are subject to influences from other senses. Here we demonstrate using single-unit recordings and estimates of mutual information that visual stimuli can influence the activity of units in the auditory cortex of anesthetized ferrets. In many cases, these units were also acoustically responsive and frequently transmitted more information in their spike disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

42
392
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 335 publications
(446 citation statements)
references
References 61 publications
42
392
3
Order By: Relevance
“…The anterior bank of the PSSC projects to the superior colliculus (Bajo et al, 2010a), and is likely to be homologous to the anterior ectosylvian sulcal field (fAES) of the cat (Jiang et al, 1996; Manger et al, 2005). In accordance with the suggestion that cat fAES may be specialized for spatial processing (Middlebrooks et al, 1998; Malhotra and Lomber, 2007; Las et al, 2008), it has been shown that inputs to the aPSSC from the visual cortex arise predominantly from area SSY (Bizley et al, 2007a), which is thought to be specialized for visual motion processing (Philipp et al, 2006). Previous studies of the PSSC have not demarcated the anterior and posterior banks.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The anterior bank of the PSSC projects to the superior colliculus (Bajo et al, 2010a), and is likely to be homologous to the anterior ectosylvian sulcal field (fAES) of the cat (Jiang et al, 1996; Manger et al, 2005). In accordance with the suggestion that cat fAES may be specialized for spatial processing (Middlebrooks et al, 1998; Malhotra and Lomber, 2007; Las et al, 2008), it has been shown that inputs to the aPSSC from the visual cortex arise predominantly from area SSY (Bizley et al, 2007a), which is thought to be specialized for visual motion processing (Philipp et al, 2006). Previous studies of the PSSC have not demarcated the anterior and posterior banks.…”
Section: Discussionsupporting
confidence: 53%
“…Previous tracer studies in ferret revealed that these areas are innervated by the ventral division of the MGB (Pallas et al, 1990), and that multiple areas, predominantly on the PEG, but also on the AEG, receive connections from the MEG (Wallace and Bajwa, 1991; Pallas and Sur, 1993; Gao and Pallas, 1999). Since these studies were completed, we have gained a deeper understanding of the functional organization of the auditory cortex as assessed by responses to both simple (Kowalski et al, 1995; Nelken et al, 2004; Bizley et al, 2005, 2007a) and complex stimuli (Nelken et al, 2008; Bizley et al, 2009, 2013; Atiani et al, 2014), warranting a more comprehensive investigation of the connectivity within the auditory cortex. Our anatomical investigations support the idea that distinct anterior and posterior processing pathways exist and extend our understanding about the organization of the auditory cortex in the ferret, thus providing crucial information to facilitate cross‐species comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations